Silat Training as a Medium for Child Character Formation - Annisa Nur Awaliyah; Susilawati Susilawati; Tomi Efendi (Eduvest - Journal of Universal Studies, 2026)
This study examines the process of character formation through silat activities based on the experience of an elementary school student named Raihan. Character education is the main goal of national education; however, its implementation in practice often emphasizes academic achievement rather than the internalization of values through real experiences. This study uses a qualitative approach with a single case study design to analyze how discipline, responsibility, and social maturity develop through long-term engagement in structured silat practice. Data collection was conducted through in-depth interviews with coaches and parents, participatory observation during training and competitions, and documentation in the form of training schedules and activity notes. The results show that discipline is developed through consistent attendance, time management, and adherence to training structures. Responsibility grows through the habituation of equipment preparation, participation in maintaining training facilities, and the execution of mentoring duties. Social maturity emerges through Raihan’s role as an assistant coach, which requires behavior management, emotional control, and leadership in social interactions. Family support and the silat community environment strengthen the continuity of the character formation process by fostering emotional stability and consistent habituation of positive attitudes. This research confirms that character formation occurs through a continuous and integrated experiential process within a supportive social ecosystem. Silat activities thus have strong potential as a medium for character education rooted in cultural practices among elementary school–age children.